The theory of scintillation with applications in remote sensing - Rino, Charles (Hoboken, N.J. : Wiley-IEEE Press, 2011)
'In order to truly understand data signals transmitted by satellite, one must understand scintillation theory in addition to well established theories of EM wave propagation and scattering. Scintillation is a nuisance in satellite EM communications, but it has stimulated numerous theoretical developments with science applications. This book not only presents a thorough theoretical explanation of scintillation, but it also offers a complete library of MATLAB codes that will reproduce the book examples. The library includes GPS coordinate manipulations, satellite orbit prediction, and earth mean magnetic field computations. The subect matter is for EM researchers; however, also theory is relevant to geophysics, acoustics, optics and astoronomy'--
'This book not only presents a thorough theoretical explanation of scintillation, but it also offers a complete library of MATLAB codes that will reproduce the book examples'--
Includes bibliographical references (p. 219-226) and index.
Keywords: Scintillation spectrometry; Remote sensing